Job creation, job destruction and firms' international trade involvement - Mauro Pisu (National Bank of Belgium, 2008)
One of the most important predictions made in recent international trade literature based on heterogeneous firms concerns the within-industry job reallocation from firms not involved in international markets to those that are. This paper quantifies the extent of this reallocation using a dataset of Belgian manufacturing firms from 1998 to 2004 providing information on their international trading activities. The results suggest that, at three-digit industry levels, the shifts in employment between firms having different trading status account for 6 to 30 percent of total job reallocation. This effect is stronger for large than for small firms.
Keywords: F16; J63; 330; Heterogeneous firms; Job reallocation; Imports; Exports; FDI; Auslandsinvestition; Import; Export; Internationaler Markteintritt; Beschäftigungseffekt; Industrie; Schätzung; Belgien